Shamanism and Psychoactives: Theory, Practice and Paradoxes of a Field Study in India - Stefano Beggiora (Psychoactives, 2025)
Since its origins, the debate on the interaction between religions and psychoactives has been strongly influenced, both positively and negatively, by prejudices, policies, fashions and trends that had little to do with scientific research. Stigma and exaltation in different historical moments have equally characterized the study of the presence and use of so-called entheogens in the different declinations of the shamanic phenomenon around the world. This article attempts to shed light on the various trends regarding the state of the art, providing new epistemological elements on the basis of an ethnographic investigation among some Indigenous peoples of India. The production of alcoholic beverages (fermented and distilled, but sometimes in combination with other psychoactive or hallucinogens among the starters) is a fundamental trait of the aboriginal (ādivāsī) cultures of the Indian subcontinent. Not immune from an attempt at political instrumentalization, which occurred both in the colonial period and in the contemporary era, the discourse on the natural production of these sacred substances is today the key to understanding indigenous ontology and its traditional idea of sustainability. Far beyond the mere documentation of the induction of altered states of consciousness, this investigation involves the discovery of local pharmacopeias, as well as principles of fermentation and food preservation.